1998
DOI: 10.1046/j.1469-8137.1998.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ozone on wild plants

Abstract: Although there is a great deal of concern about the effects of human activities on biodiversity, until recently there has been very little interest in the effects of ozone on the species that constitute the major part of the flora, the diverse herbaceous and shrubby species of natural and semi-natural communities. However, many wild species have been shown to be at least as sensitive to ozone as crops that show significant yield losses, so there is a pressing need for an evaluation of the risk to wild s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
126
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 220 publications
(136 citation statements)
references
References 117 publications
6
126
1
Order By: Relevance
“…This suggests that natural selection for O $ resistance may have occurred, although additional factors cannot be discounted (Davison & Barnes, 1998). Furthermore, enhanced resistance to O $ was observed in two populations over a 6-yr period coinciding with a period of high O $ levels, thus demonstrating the strength of selection ; see also Whitfield et al, 1997 for demonstration of selection potential).…”
Section: mentioning
confidence: 92%
See 3 more Smart Citations
“…This suggests that natural selection for O $ resistance may have occurred, although additional factors cannot be discounted (Davison & Barnes, 1998). Furthermore, enhanced resistance to O $ was observed in two populations over a 6-yr period coinciding with a period of high O $ levels, thus demonstrating the strength of selection ; see also Whitfield et al, 1997 for demonstration of selection potential).…”
Section: mentioning
confidence: 92%
“…At present little is known about the genetics of O $ resistance, but some progress is being made in understanding the biochemistry of resistance (Reiling & Davison, 1994Davison & Barnes, 1998 ;Lyons et al, 1999). Lyons et al (1997Lyons et al ( , 1999 conclude that factors such as biochemical detoxification and repair processes must have been important in their study.…”
Section: mentioning
confidence: 99%
See 2 more Smart Citations
“…In the sixth experiment, a slight increase of the total biomass of Iraí cultivar seedlings (p = 0.098) was observed at exposure to approximately 147 ppb h ( Figure 4B). Although ozone and its reaction products are known to reduce photosynthesis and change the carbohydrate allocation, causing a reduced accumulation of biomass (Rennenberg et al, 1996), this generally occurs over the longer term, as suggested by Davison and Barnes (1998).…”
Section: Dry Mass Accumulationmentioning
confidence: 99%